Pengaruh Proporsi Tepung Biji Alpukat dan Madu Terhadap Sifat Organoleptik Masker Wajah Tradisional - Farrah Zafira; Biyan Yesi (Journal of Beauty and Cosmetology (JBC), 2021)
Avocado seeds contain phenolic, tannin and flavonoid so that it can be used as an ingredient of face mask. The aims of this research were 1) to know the effect of avocado seeds flour and honey proportion on the organoleptic properties of mask including color, smell, texture, viscosity, stickiness and panelist preferences; 2) determine the best proportion of avocado seeds flour and honey on the organoleptic properties of mask. Type of this research was experiment. The independent variable was proportion of avocado seeds flour and honey, they are X1 (5g:10g), X2 (6g:9g), and X3 (7g:8g). The dependent variables were physical properties of mask including color, smell, texture, viscosity, stickiness and panelist preferences. Data collection for physical properties of traditional face mask was conducted by observation method performed by 30 panelists. One way varian analysis conducted to know the effect of avocado seeds flour and honey proportion on the organoleptic properties and continued with Duncan test using the SPSS 25 program. Research results show that there is an effect of the proportion of avocado seeds flour and honey on the organoleptic properties of traditional face mask for color, smell, texture, viscosity, stickiness and panelist preferences. The result of the best face mask is face mask with proportion of avocado seeds flour 5g and honey 10g with criteria that is color was orange brown, slightly smelled of avocado seeds flour, textured smooth, sticky, adhesive and very like by the panelist. Keywords: Face Mask; Avocado Seeds Flour; Honey